Diplecogaster tonstricula, a new species of cleaning clingfish (Teleostei: Gobiesocidae) from the Canary Islands and Senegal, eastern Atlantic Ocean, with a review of the Diplecogaster-ctenocrypta species-group. Issue 11 (26th March 2016) - Fricke, Ronald; Wirtz, Peter; Brito, Alberto
ABSTRACT: The Diplecogaster-ctenocrypta species-group is reviewed; it comprises two species. The clingfish Diplecogaster ctenocrypta from the Canary Islands is redescribed. The new species Diplecogaster tonstricula, a facultative cleaner of other teleosts, is described on the basis of eight specimens and colour photos from Senegal and the Canary Islands, eastern Atlantic Ocean. The species is small, apparently not exceeding 23 mm total length; it is characterised by having nine dorsal-fin rays, eight anal-fin rays, 24–25 pectoral-fin rays, 14–15 principal caudal-fin rays, 13–16 rakers on third gill arch, pelvic disc without lateral papillae in region A, disc region B with two rows of weak papillae, interorbital distance 4.1–4.6 in head length, distance between disc and anus 14–17% of SL, head and body with 10–13 narrow vertical brownish bars, cheek with a white ocellus surrounded by black, and with a small black spot in the middle. The new species is compared with other species of the genus; a key to the six known species of the eastern Atlantic, Mediterranean and Black Sea and South African genus Diplecogaster is presented. A checklist is provided for the species of Diplecogaster and their synonyms.